Sitagliptin Modulates Oxidative, Nitrative and Halogenative Stress and Inflammatory Response in Rat Model of Hepatic Ischemia-Reperfusion - Małgorzata Trocha; Mariusz G. Fleszar; Paulina Fortuna; Łukasz Lewandowski; Kinga Gostomska-Pampuch; Tomasz Sozański; Anna Merwid-Ląd; Małgorzata Krzystek-Korpacka (Antioxidants, 2021)
A possibility of repurposing sitagliptin, a well-established antidiabetic drug, for alleviating injury caused by ischemia-reperfusion (IR) is being researched. The aim of this study was to shed some light on the molecular background of the protective activity of sitagliptin during hepatic IR. The expression and/or concentration of inflammation and oxidative stress-involved factors have been determined in rat liver homogenates using quantitative RT-PCR and Luminex® xMAP® technology and markers of nitrative and halogenative stress were quantified using targeted metabolomics (LC-MS/MS). Animals (n = 36) divided into four groups were treated with sitagliptin (5 mg/kg) (S and SIR) or saline solution (C and IR), and the livers from IR and SIR were subjected to ischemia (60 min) and reperfusion (24 h). The midkine expression (by 2.2-fold) and the free 3-nitrotyrosine (by 2.5-fold) and IL-10 (by 2-fold) concentration were significantly higher and the Nox4 expression was lower (by 9.4-fold) in the IR than the C animals. As compared to IR, the SIR animals had a lower expression of interleukin-6 (by 4.2-fold) and midkine (by 2-fold), a lower concentration of 3-nitrotyrosine (by 2.5-fold) and a higher Nox4 (by 2.9-fold) and 3-bromotyrosine (by 1.4-fold). In conclusion, IR disturbs the oxidative, nitrative and halogenative balance and aggravates the inflammatory response in the liver, which can be attenuated by low doses of sitagliptin.